Intravenous treatment with rimiterol and salbutamol in asthma. Issue 5973 (28th June 1975) - Marlin, G E; Turner, P
Abstract : The bronchodilating efficacies and beta2-adrenoceptor selectivities of rimiterol (0.2, 0.1, and 0.05 mug kg-minus1 min-minus1) and sal-utamol (0.1, 0.5, and 0.025 mug kg-minus1 min-minus1), intravenously infused for one hour, were determined in five patients with chronic asthma. Each drug infusion produced and maintained a dose-related improvement in forced expiratory volune in one second (FEV1). A further increase in FEV1 was produced by inhalation of the same drug by pressurized aerosol at the end of each infusion, which suggested that no resistance had occurred. Similar dose-related increases in heart rate, pulse pressure, and skeletal muscular tremor were produced by each drug. Peak heart rate increases varied greatly between individuals, ranging from 12 to 30 beats/min with the high doses but always less than 10 beats/min with the low doses of each drug. On rimiterol the heart rate reached equilibrium earlier during the infusions and declined more rapidly after they had stopped, thus providing an accurate means for monitoring dosage. Rimeterol with its short half life-a desirable property for an intravenous drug with respect to safety-may prove to be a valuable bronchodilator in severe asthma when intravenous infusions are indicated.